PENGARUH KUALITAS KEHIDUPAN KERJA TERHADAP KEPUASAN KERJA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA PT. PERKEBUNAN NUSANTARA V UNIT LUBUK DALAM-SIAK - Genna Anggini Erzend; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the effect of quality of work life on job satisfaction with work motivation as an intervening variable at PT. Perkebunan Nusantara V Lubuk Dalam Unit-Siak. The independent variable is the quality of work life (X) and the intervening variable is work motivation (Z). While what is used as the dependent variable (Y) is job satisfaction. The study used a questionnaire with a measurement scale using a likert scale. The analysis technique used is SEM and PLS analysis. Data analysis using linear regression analysis with the help of SmartPLS 3.0 software.               The population in this study were 84 employees of PT. Perkebunan Nusantara V Lubuk Dalam Unit-Siak obtained using the Slovin formula. From the results of tests conducted showed that the quality of work life has a positive and significant effect on job satisfaction, the quality of work life has a positive and significant effect on work motivation, work motivation has a positive and significant effect on job satisfaction and the quality of work life has a positive and significant effect on job satisfaction with work motivation as an intervening variable.